Gleaning, Drying and Marketing Practices of Sea Cucumber in Davao Del Sur, Philippines - Subaldo, Milagros C. (JPAIR Multidisciplinary Research, 2011)
Gleaning, drying and marketing practices of sea cucumber in Davao del Sur was conducted to document the local practices, common species gathered and to identify problems along with the adopted practices. Results disclosed that gleaning was done by skin diving with the use of air compressor or hand picking in intertidal reef flats during low tide. Species usually gathered includes Stichopus horrens, Holuthuria scabra, Stichopus hermani, Thelonota anax, Holothuria fuscolgiva, Holothuria fuscopunctata, Bohadschia marmorata and Holothuria whitmaei. Drying process for beche-de-mer production includes washing, evisceration, washing, boiling, soaking in brine solution, smoke drying and sun drying. However, soaking in brine solution was practiced only by processors in the 1st District of the province purposely to extend its shelf-life. Selling was done in "all-in" basis, cash upon delivery and buyers were the one dictating the market price. Flows of dried sea cucumber from processors were through wholesalers coming from Digos City and Davao City and shipped to Manila and Korean markets. Problems identified along with the adopted practices were nonselection as to size utilized for consumption or for sale. Also, problems on poor drying practices, packaging materials used non-utilization of entrails and disposal of waste.